Time-Dependent Load-Reduction Performance of High-Fill Box Culverts Equipped with Top and Side EPS layers - Bao-Guo Chen; Zhen-Zhong Yang; Ding-Bao Song; Yi-Qing Ren; Qiang Ma (Computers and Geotechnics, 2026)

Physics-inspired perspective on synergistic optimization: a deep receding-horizon optimization strategy for denitrification and ammonia slip suppression in waste incineration - Xiaoqing Lin; Ren Wang; Yuxuan Zhou; Yunfeng Ma; Jie Chen; Chengwei Zhou; Wei Zhong; Qunxing Huang; Xiaodong Li; Jianhua Yan (Bioresource Technology, 2026)

Dual-role ultrasonication in fabricating a zein-resveratrol/pectin complex: From particle engineering to interface activation for superior pickering emulsion stability - Qiufang Liang; Panpan Cao; Yunxia Du; Aosen Lu; Haile Ma; Mingming Zhong; Yufan Sun; Abdul Qayum; Xiaofeng Ren (Food Chemistry, 2026)

Fabrication of polymeric bigels with locust bean gum and clove essential oil using tri-frequency ultrasonication to enhance the dispersion and gel properties for functional applications - Muhammad Awais; Jawad Ashraf; Muhammad Safiullah Virk; Sanabil Yaqoob; Qiufang Liang; Yufan Sun; Aysha Imtiaz; Mingming Zhong; Wenjing Zhu; Haile Ma; Xiaofeng Ren (Food Hydrocolloids, 2026)

Injectable ECM-mimetic hydrogels enable coordinated mitochondrial rejuvenation of senescent nucleus pulposus cells for repairing degenerative intervertebral discs - Jiayi Zhang; Chi Ma; Haifeng Zhang; Haibing Wang; Siya Wang; Xueting Ren; Licheng Zhang; Menghuan Li; Zhong Luo; Xiang Cui (Chemical Engineering Journal, 2026)

3D Formicary-like Carbon Derived from Lotus Leaf Stem for High-performance Textile Dye Adsorbent - Nan Jiang; Tianxiao Ma; Xiaohui Zhong; Yiming Ren; Huan Liu (Water, Air, & Soil Pollution, 2026)

Agricultural anthropogenic attribution of nitrate in karst river basin: Insights from nitrate dual isotopes and Bayesian mixing model - Xinyi He; Jie Zeng; Qixin Wu; Qian Zhang; Zhong-Jun Wang; Jie Ren; Qing Ma; Jie Zhang; Xin Ge (Journal of Environmental Management, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

Volatile metabolomics and Metaproteomics reveal key flavor formation mechanisms in mixed-culture fermented Rice slurry - Yuanyuan Ren; Yingjie Lei; Rui He; Jin Fu; Ding Ma; Geng Zhong (Food Research International, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Time-dependent dynamics of starch structure, functionality and quality in rice noodles during inoculated fermentation - Yuanyuan Ren; Yingjie Lei; Rui He; Jin Fu; Ding Ma; Geng Zhong (Carbohydrate Polymers, 2026)

Assessing road network resilience to extreme rainstorms: A percolation and hydrodynamic approach - Fei Ma; Rong Fu; Wei Ren; Qing-Chang Lu; Qing Liu; Zhijie Yang; Zhong Ma (Transportation Research Part D: Transport and Environment, 2026)

Effects of multifrequency ultrasound assisted pH extraction on the interfacial characteristics and tribological performance of soybean oleosomes - Yufan Sun; Mingming Zhong; Qin Liu; Qingzhen Liang; Qiufang Liang; Xinyu Chen; Haile Ma; Xiaofeng Ren (Food Research International, 2026)

Synergistic effects of climate forcings from three oceans on the reserve of “Atmospheric water tower” over the Tibetan Plateau - Pengjie Ren; Wusheng Yu; Stephen Lewis; Yaoming Ma; Yuanyuan Dang; Lei Zhong; Zhuanxia Zhang; Yong Liu; Lun Luo; Zhaowei Jing; Jingyi Zhang; Rong Guo; et al. (Journal of Hydrology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Deciphering microbial and metabolite dynamics in rice noodle fermentation: A metagenomic and untargeted metabolomic approach - Yuanyuan Ren; Yuhang Li; Yingjie Lei; Rui He; Jin Fu; Ding Ma; Geng Zhong (Food Chemistry, 2025)

Ultrasonic-assisted preparation of resistant starch: advances in methods, structural properties, functional characteristics, and applications - Qiufang Liang; Yunxia Du; Panpan Cao; Mingming Zhong; Yufan Sun; Haile Ma; Husnain Raza; Xiaofeng Ren (Food Chemistry, 2025)

Preparation of omniphobic membrane by anchoring hydrophobic islands at fixed-points for treating hypersaline wastewater - Ronghua Ma; Xiaolong Lu; Jie Gu; Kai Ren; Yuling Ren; Yuefei Song; Zhong Ma (Desalination, 2025)

Protein-driven multiscale structural evolution and oil absorption in Tigernut (Cyperus esculentus L.) starch during thermal extrusion - Xiao-Shuang Cai; Jing-Wen Qin; Zhong-Wei Wu; Wan-Tong Zhao; Wen-Ting Yin; Yu-Xiang Ma; Hua-Min Liu; Jing-Ren He (Carbohydrate Polymers, 2025)

Group 2 innate lymphoid cells derived IL-9 reduces macrophage apoptosis and attenuates acute lung injury in sepsis - Xiaohui Zhong; Jingyi Jin; Hang Zhang; Zhicong Liu; Yichao Ren; Yi Xiao; Yuebai Zhang; Sisi Yang; Shu Fang; Nan Lin; Ping Cui; Daqing Ma; et al. (Inflammation Research, 2025)

Effects of fermentation by different strains on the Physico- chemical properties, quality, and metabolic profile of Rice noodles - Yuanyuan Ren; Yuhang Li; Rui He; Yingjie Lei; Yi Zhao; Zikuan Meng; Ding Ma; Jin Fu; Geng Zhong (Food Chemistry, 2025)

Bifunctional flow-through electrified-membrane for intensified confined hydroxyl radical generation and efficient pollutant degradation - Junwen Chen; Qiming Zhang; Shuang Zhong; Hongyu Zhou; Wei Ren; Lei Shi; Tianyi Ma; Shaobin Wang; Xiaoguang Duan (Chemical Engineering Journal, 2025)

Microplastics Induce Structural Color Deterioration in Fish Poecilia reticulata Mediated by Oxidative Stress - Hong-Yu Ren; Huan-Chao Ma; Rui-Peng He; Cong-Cong Gao; Bin Wen; Jian-Zhong Gao; Zai-Zhong Chen (Fishes, 2025)
Microplastics (MPs) can affect fish health by inducing oxidative stress, but their impact on structural coloration remains poorly understood. This study investigated the effects of environmentally relevant concentrations (16 and 160 μg/L) of MPs and nanoplastics (NPs) exposure on growth, oxidative stress and structural coloration in blue strain guppy fish (Poecilia reticulata). Results showed exposure to 160 μg/L MPs significantly reduced specific growth rate of fish compared to controls. Plastic accumulation followed a dose-dependent pattern, especially within gut concentrations. Oxidative stress responses differed between MPs and NPs: 160 μg/L MPs decreased SOD activity in skin and reduced GSH levels, while 160 μg/L NPs increased MDA levels in gut tissues, indicating severe lipid peroxidation. Structural coloration analysis revealed exposure to 160 μg/L MPs decreased lightness and increased yellowness, demonstrating reduced blue coloration. This was accompanied by an increase in skin uric acid content, suggesting that guanine conversion might occur to combat oxidative stress. These findings demonstrate that MPs, particularly at high concentrations, impair growth and induce oxidative stress in guppies. To counteract stress, guanine in iridophores may be converted into uric acid, leading to a decline in structural coloration. This study is the first to reveal that MPs disrupt structural coloration of fish, providing new insights into the ecological risks of plastic pollution on aquatic organisms.

The Impact of Gray Matter Structural Changes on Clinical Disability in Multiple Sclerosis: Voxel-and Surface-Based Analyses - Hongping Chen; Weihua Zhang; Yuchao Ma; Jiayun Ren; Di Zhong (Neuroinformatics, 2025)

Occurrence, spatial distributions, sources, and potential risks of organophosphate esters in Yarlung Tsangpo River and its main tributaries on the Tibetan Plateau - Mingyu Zhong; Menghan Zhou; Jianhui Tang; Jiao Ren; Ruixue Ma; Xiaole Li (Environmental Pollution, 2025)

Dietary phytic acid damages the intestinal mucus barrier and structural integrity in the grass carp (Ctenopharyngodon idella) - Daiyu Chen; Jingren Zhong; Weidan Jiang; Pei Wu; Yaobin Ma; Yang Liu; Hongmei Ren; Xiaowan Jin; Xiaoqiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2025)

NiVOx/BiVO4 photoanode for stable photoelectrochemical water splitting: Reconstruction of Ni and V to form active sites and V-rich electrolyte - Xing Cao; Lanxing Ren; Yubin Zhao; Huanhui Chen; Ziqian Lu; Ya Liu; Shoujing Wei; Qing Ma; Liubiao Zhong; Lijuan Song; Yejun Qiu (Chemical Engineering Journal, 2025)

The interaction of atmospheric boundary layer and PM pollution in Mongolian Plateau: Implication for the threshold control strategy - Simin Yang; Yongjing Ma; Wenyu Zhang; Zhong Lin; Zhenguo Lu; Xingjun Zhou; Yuanzhe Ren; Xinbing Ren; Kecheng Peng; Yulong Tan; Yiming Wei; Masroor Ahmad; et al. (Atmospheric Research, 2025)

Developments and application of fish school swimming model in recirculating aquaculture systems - Gang Wu; Hai-Bo Liu; Chao Ma; Heng-Ming Xu; Xiao-Zhong Ren; Wei Sun (Ocean Engineering, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Longitudinal landscape of immune reconstitution after acute SARS-CoV-2 infection at single-cell resolution - Lili Ren; Yiwei Liu; Yeming Wang; Chao Wu; Li Guo; Lan Chen; Xinming Wang; Yan Xiao; Lixue Huang; Jingchuan Zhong; Jiacheng Yao; Lu Liu; et al. (Science Bulletin, 2025)

Shared responsibility for carbon emission reduction in worldwide “steel- electric vehicle” trade within a sustainable industrial chain perspective - Yanxin Liu; Huajiao Li; Huijun Ren; Hongdian Jiang; Bo Ren; Ning Ma; Zhensong Chen; Weiqiong Zhong; Sergio Ulgiati (Ecological Economics, 2025)

Carbon-based materials in flow-through electro-fenton: Advanced catalyst design, mechanisms and perspectives - Junwen Chen; Wei Ren; Shuang Zhong; Hongyu Zhou; Tianyi Ma; Shaobin Wang; Xiaoguang Duan (Chemical Engineering Journal, 2024)

Exploring the interface dynamics of emulsion gel via a novel non-destructive technique provides insights into the underlying mechanism of gel formation, water mobility, functionality and structural variations - Abdul Qayum; Arif Rashid; Asif Ali Khan; Mingming Zhong; Yuxuan Liu; Muhammad Hussain; Muhammad Safiullah Virk; Zahoor Ahmed; Abdur Rehman; Abid Hussain; Qiufang Liang; Xiaofeng Ren; et al. (Food Bioscience, 2024)

Improving the CO2 permeability and selectivity of Pebax mixed-matrix membranes by constructing an "expressway" using pyrazine-based nitrogen-doped porous carbon with nitrogen-containing groups and meso-microporous structure - Peilin Li; Wenzhong Ma; Jing Zhong; Yang Pan; Xiuxiu Ren; Meng Guo; Nanhua Wu; Hideto Matsuyama (Journal of Environmental Chemical Engineering, 2024)

Study of boundary layer parameterization simulation uncertainties of sand-dust storm windfield using high-resolution three-dimensional Doppler wind lidar data - Lei Zhang; Jinyuan Xin; Yan Yin; Ruixia Liu; Yongli Tian; Zhong Lin; Xingjun Zhou; Yuanzhe Ren; Xin Zhang; Yongjing Ma; Xinbing Ren; Dandan Zhao; et al. (Atmospheric Research, 2024)

Partially knocking out NtPDK1a/1b/1c/1d simultaneously in Nicotiana tabacum using CRISPR/CAS9 technology results in auxin-related developmental defects - Qian-Wei Ren; Tian-Yao Liu; Hu-Jiao Lan; Zhen-Chao Li; Min-Jun Huang; Ya-Ting Zhao; Yu Chen; Li-Na Liao; Xiao-Han Ma; Jian-Zhong Liu (Plant Science, 2024)

Phycosphere bacterial disturbance of Saccharina japonica caused by white rot disease relates to seawater nutrients - Chen Ma; Chengxiang Peng; Longwen Fu; Chenggang Ren; Xintian Liu; Zhengyi Liu; Song Qin; Zhihai Zhong (Environmental Science and Pollution Research, 2024)

Research progress in soybean lipophilic protein (LP): Extraction, structural, techno-functional properties, and high-performance food applications - Mingming Zhong; Yufan Sun; Abdul Qayum; Qiufang Liang; Abdur Rehman; Renyou Gan; Haile Ma; Xiaofeng Ren (Trends in Food Science & Technology, 2024)

Magnetic photoelectrochemical sensor array utilizing addressing sensing strategy for simultaneous detection of amyloid-β 42 and microtubule-associated protein tau - Shuo Zhang; Yunfei Zhang; Huan Wang; Yaoguang Wang; Hongmin Ma; Dan Wu; Zhong Feng Gao; Dawei Fan; Xiang Ren; Qin Wei (Analytica Chimica Acta, 2024)

The Role of Ubiquitin–Proteasome System and Mitophagy in the Pathogenesis of Parkinson's Disease - Yu Liang; Guangshang Zhong; Mingxin Ren; Tingting Sun; Yangyang Li; Ming Ye; Caiyun Ma; Yu Guo; Changqing Liu (NeuroMolecular Medicine, 2023)

Hemispheric coupling between structural and functional asymmetries in clinically asymptomatic carotid stenosis with cognitive impairment - Chenhong Fan; Dan Xu; Hao Mei; Xiaoli Zhong; Jinxia Ren; Jiaojiao Ma; Zhao Ruan; Jinfeng Lv; Xitong Liu; Huan Wang; Lei Gao; Haibo Xu (Brain Imaging and Behavior, 2023)

The improvement of the oxidative oat (Avena sativa L.) protein based on ultrasound treatment: Study of structural, emulsifying, and rheological properties - Yue Xu; Yang Yang; Chun-min Ma; Xin Bian; Li-Kun Ren; Bao-xiang Liu; Lian-zhong Ai; Na Zhang (Food Hydrocolloids, 2023)

Targeted control of soil erosion through selective regulation of Eleocharis yokoscensis using mixed endophytes - Qifeng Gao; Xiao Xiao; Ting Liu; Zhong Ren; Wei Ren; Yunya Zhan; Wenqian Wang; Weiran Feng; Li Ma; Le Qi; Zixian Zhang; Xubiao Luo; et al. (CATENA, 2023)

High-resolution distributions of traffic particles and personal inhalation dose estimation at different pedestrian overpasses - Wenbin Yang; Ruhui Cao; Fan Ma; Zhanyong Wang; Xisheng Hu; Ming Cai; Zhong-Ren Peng; Yiqiang Wei; Jinqiang Xu; Lanyi Zhang (Atmospheric Pollution Research, 2023)

Grain boundary capacitance effect in Iron-based magnetic composites for superior C-band microwave absorption - Chengshuai Shao; Chunyan Ding; Yu Liu; Yu Ma; Long Zhang; Xiaozhen Ren; Songsong Wu; Bo Zhong; Guangwu Wen; Xiaoxiao Huang (Chemical Engineering Journal, 2023)

Genesis of Lower Cretaceous lacustrine pistomesite in Baiyinchagan Sag, Erlian Basin, China: evidence from mineralogy and geochemical characteristics - Chen Su; Dakang Zhong; Yanyan Ma; Su Huang; Peng Qin; Xi Ren (Arabian Journal of Geosciences, 2022)

High-speed and efficient removal of uranium (VI) from aqueous solution by hydroxyapatite-modified ordered mesoporous carbon (CMK-3) - Ming Ma; Hao Deng; Zhenyu Ren; Xin Zhong (Environmental Science and Pollution Research, 2022)

Two metabolites isolated from endophytic fungus Coniochaeta sp. F-8 in Ageratina adenophora exhibit antioxidative activity and cytotoxicity - Jie Fu; Liwen Hu; Zhen Shi; Wei Sun; Dong Yue; Ya Wang; Xiaoping Ma; Zhihua Ren; Zhicai Zuo; Guangneng Peng; Zhijun Zhong; Junliang Deng; et al. (Natural Product Research, 2021)

Protective effect of MitoQ on oxidative stress-mediated senescence of canine bone marrow mesenchymal stem cells via activation of the Nrf2/ARE pathway - Lijun Zhong; Jiaqiang Deng; Congwei Gu; Liuhong Shen; Zhihua Ren; Xiaoping Ma; Qigui Yan; Junliang Deng; Zhicai Zuo; Ya Wang; Suizhong Cao; Shumin Yu (In Vitro Cellular & Developmental Biology - Animal, 2021)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

The therapeutic potential of bilobalide on experimental autoimmune encephalomyelitis (EAE) mice - Qiang Miao; Xiao-Xue Zhang; Qing-Xian Han; Si-Si Ren; Ruo-Xuan Sui; Jing-Wen Yu; Jing Wang; Qing Wang; Jie-Zhong Yu; Liang Cao; Wei Xiao; Bao-Guo Xiao; et al. (Metabolic Brain Disease, 2020)

MiR-26a promotes fracture healing of nonunion rats possibly by targeting SOSTDC1 and further activating Wnt/β-catenin signaling pathway - Liang Sun; Zhong Li; Hanzhong Xue; Teng Ma; Cheng Ren; Ming Li; Yao Lu; He Sun; Kun Zhang (Molecular and Cellular Biochemistry, 2019)

QTL analysis of delayed maize flowering in response to low phosphate across multi-environments - Zhiyong Ren; Xiao Zhang; Hailan Liu; Wenjun Liu; Zhi Nie; Dan Liu; Ling Wu; Haijian Lin; Shunzong Su; Duojiang Gao; Bowen Luo; Peng Ma; et al. (Euphytica, 2019)

Standardized Operational Protocol for Human Brain Banking in China - Wenying Qiu; Hanlin Zhang; Aimin Bao; Keqing Zhu; Yue Huang; Xiaoxin Yan; Jing Zhang; Chunjiu Zhong; Yong Shen; Jiangning Zhou; Xiaoying Zheng; Liwei Zhang; et al. (Neuroscience Bulletin, 2019)

Immunogenicity of adenovirus and DNA vaccines co-expressing P39 and lumazine synthase proteins of Brucella abortus in BALB/c mice - Guo-Zhen Lin; Ju-Tian Yang; Suo-Cheng Wei; Shi-En Chen; Sheng-Dong Huo; Zhong-Ren Ma (Tropical Animal Health and Production, 2018)

Molecular characterization of a stress-induced NAC gene, GhSNAC3, from Gossypium hirsutum - Zhan-Ji Liu; Fei Li; Li-Guo Wang; Ren-Zhong Liu; Jun-Jun Ma; Ming-Chuan Fu (Journal of Genetics, 2018)

In vitro and in vivo studies of nematophagous fungi Arthrobotrys musiformis and Arthrobotrys robusta against the larvae of the trichostrongylides - Kui Zheng Cai; Bo Bo Wang; Qiang Xu; Jun Lin Liu; Kang Ying Wang; Yu Jia Xue; Hai Yan Zhang; Hai Yu Wang; Xin Cao; Zhong Ren Ma (Acta Parasitologica, 2017)
Six isolates of

28-Day hindlimb unweighting reduces expression of Rho kinase and inhibits its effects in femoral artery of rat - Zhong-Chao Wang; Huan Liu; Yun-Gang Bai; Jin-Wen Yu; Hai-Jun Zhang; Yao-Ping Cheng; Jun-Xiang Bao; Xin-Ling Ren; Hong-Zhe Ma; Jin Ma (Journal of Physiology and Biochemistry, 2015)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

Identification and genetic mapping of the putative Thinopyrum intermedium-derived dominant powdery mildew resistance gene PmL962 on wheat chromosome arm 2BS - X. K. Shen; L. X. Ma; S. F. Zhong; N. Liu; M. Zhang; W. Q. Chen; Y. L. Zhou; H. J. Li; Z. J. Chang; X. Li; G. H. Bai; H. Y. Zhang; et al. (Theoretical and Applied Genetics, 2015)

Cloning, characterization and expression of chalcone synthase from medicinal plant Rhus chinensis - Wenli Ma; Yang Wu; Min Wu; Zhumei Ren; Yang Zhong (Journal of Plant Biochemistry and Biotechnology, 2015)

Haplotype analysis of TLR4 gene and its effects on milk somatic cell score in Chinese commercial cattle - Xing Ping Wang; Zhuo Ma Luoreng; Shu Xin Gao; Dong Sheng Guo; Jun Ya Li; Xue Gao; Shang Zhong Xu; Feng Li; Gang Chen; Jin Ren Wang (Molecular Biology Reports, 2014)

Polycyclic aromatic hydrocarbons in water, sediment and soil of the Songhua River Basin, China - Wan-Li Ma; Li-Yan Liu; Hong Qi; Zi-Feng Zhang; Wei-Wei Song; Ji-Min Shen; Zhong-Lin Chen; Nan-Qi Ren; Josey Grabuski; Yi-Fan Li (Environmental Monitoring and Assessment, 2013)

The effects of the codon usage and translation speed on protein folding of 3Dpol of foot-and-mouth disease virus - Xiao-xia Ma; Yu-ping Feng; Jun-lin Liu; Bing Ma; Li Chen; Yong-qing Zhao; Peng-hui Guo; Jun-zhen Guo; Zhong-ren Ma; Jie Zhang (Veterinary Research Communications, 2013)

Cloning and characterisation of a phenylalanine ammonia-lyase gene from Rhus chinensis - WenLi Ma; Min Wu; Yang Wu; ZhuMei Ren; Yang Zhong (Plant Cell Reports, 2013)

Ethylene Interacts with Auxin in Regulating Developmental Attenuation of Gravitropism in Flax Root - Zhong Ma; Yu-yu Ren (Journal of Plant Growth Regulation, 2012)

Roles of arabinogalactan proteins in cotyledon formation and cell wall deposition during embryo development of Arabidopsis - Jing Zhong; YuJun Ren; Miao Yu; TengFei Ma; XueLian Zhang; Jie Zhao (Protoplasma, 2011)

Population genetic structure and phylogeographical pattern of rice grasshopper, Oxya hyla intricata, across Southeast Asia - Tao Li; Min Zhang; Yanhua Qu; Zhumei Ren; Jianzhen Zhang; Yaping Guo; K. L. Heong; Bong Villareal; Yang Zhong; Enbo Ma (Genetica, 2011)

Assessing heavy-metal contamination and sources by GIS-based approach and multivariate analysis of urban–rural topsoils in Wuhan, central China - Min Gong; Li Wu; Xiang-yang Bi; Li-min Ren; Lei Wang; Zhen-dong Ma; Zheng-yu Bao; Zhong-gen Li (Environmental Geochemistry and Health, 2010)

Comparative population structure of Chinese sumac aphid Schlechtendalia chinensis and its primary host-plant Rhus chinensis - Zhumei Ren; Bin Zhu; Dingjiang Wang; Enbo Ma; Deming Su; Yang Zhong (Genetica, 2007)